Island ecology and evolution: challenges in the Anthropocene - GRAHAM, NATALIE R.; GRUNER, DANIEL S.; LIM, JUN Y.; GILLESPIE, ROSEMARY G. (Environmental conservation, 2017)
Islands are widely considered to be model systems for studying fundamental questions in ecology and evolutionary biology. The fundamental state factors that vary among island systems – geologic history, size, isolation and age – form the basis of mature phenomenological and predictive theory. In this review, we first highlight classic lines of inquiry that exemplify the historical and continuing importance of islands. We then show how the conceptual power of islands as ‘natural laboratories’ can be improved through functional classifications of both the biological properties of, and human impact on, insular systems. We highlight how global environmental change has been accentuated on islands, expressly because of their unique insular properties. We review five categories of environmental perturbation: climate change, habitat modification, direct exploitation, invasion and disease. Using an analysis of taxonomic checklists for the arthropod biotas of three well-studied island archipelagos, we show how taxonomists are meeting the challenge of biodiversity assessment before the biodiversity disappears. Our aim is to promote discussion on the tight correlations of the environmental health of insular systems to their continued importance as singular venues for discovery in ecology and evolutionary biology, as well as to their conservation significance as hotspots of endemism.